HASIL BELAJAR KOGNITIF MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING - Sasmaya, Rizky Oka; Kashardi, Kashardi; Zachriwan, Zachriwan (Universitas Muhammadiyah Bengkulu, 2020)
This study aims to determine whether the Snowball Throwing learning model can improve students' cognitive learning outcomes in quadrilateral and triangle material class VII A of Middle School 3 Kepahiang. The type of research used in this study is class action research the model of Kurt Lewin through four stages, namely: planning, action, observation and reflection. The research subjects were all students of class VII A of SMP 3 Kepahiang consisting of 26 students. This research was conducted from january 23 to February 13, 2019. Data collection techniques in this study were observations and tests, with research instruments observation sheets and test sheets. Data analysis techniques in this study used descriptive statistics, namely by percentage. Based on the observation sheet, the teacher's activity in the third cycle of teacher activity is classified as a good criterion and, every aspect has been in sufficient complexity. Based on the results of the evaluation test in Cycle III classical completeness was . Based on the results of the third cycle that has met the indicators of success, the research was stopped. Thus it can be concluded that the application of the Snowball Throwing learning model is well implemented and can improve students' cognitive learning outcomes in quadrilateral and triangular material in class VII AKepahiang 3 Public Middle School.Keywords: Snowball Throwing, Cognitive Learning OutcomesÂ